BATI MÜZİĞİNİN TÜRKİYE'YE GİRİŞİ VE ETKİLERİ - ÖZDEMİR, NURETTİN (Fırat Üniveristesi, 2012)
Müzik, insanların sosyal yönlerini ortaya koyduğu ve toplumsal etkileşimlere yol açan bir olgudur. İnsanoğlu dünya kurulduğundan itibaren müzik öğrenmeye, müzik yapmaya çalışmıştır. Doğada çıkan sesleri taklit yoluna giderek, hayvanlardan çıkan seslere benzer sesleri ortaya koyarak ve özel günlerde bunları sergileyerek müziğin temellerini atmışlardır. Hayvan derilerinden ve doğada bulunan kütüklerden enstrümana benzer aletler yapmışlardır. Zamanla müzik, insanların duygularını dışa vurmaları için kullandıkları sosyal bir nesne haline dönüşmüştür.Müzik insanları, insanlar da kültürleri etkilemiştir. Batı müziği de coğrafyamıza belli bir süreçte girmiş ve izler bırakmıştır.Osmanlının son yüzyılında kültürümüze Batı Müziği, Cumhuriyet döneminde eğitim ve kültür ?sanat politikaları da oldukça önemsenmiştir.Anahtar Kelimeler: Müzik, Bibliyografya, Muzika-i Hümayun, Çok Sesli Müzik, Cumhuriyet Dönemi Müzik

Music is a phenomenon which people introduce their social sides ending up with social interaction. Since the human being settled to earth they have started to learn music and make music. Of course, this situation needs to be held in terms of current conditions. People founded the music by imitating the natural sounds, such as producing animal sounds, and by presenting these sounds in special days. As a preparation for their presentations, people used to make primitive instruments with leather and logs existing in nature. With the lapse of time music has become a social item which is used for extracting people?s emotions.Music has a big role to shape the culture as it affects people and the people affect the culture. As it is going to be mentioned in this thesis, introduction of Western music which is a form of the music in our area and the development of this process is going to be explained.Within their westernization process, The Ottoman Empire introduced a lot of innovations and put them into their lifestyles. Afterwards, the development of the process in Republic referencing quotes from Mustafa Kemal Atatürk is going to be handled.Key Words: Music, Muzika-İ Humayun, Polyphonic Music, Music İn Turkish Republic
The access and effect of west music in Turkish republic
Keywords: Müzik